Assessing adherence and persistence to non-vitamin k antagonist oral anticoagulants (NOACs) among patients with atrial fibrillation in tertiary-care referral centers in Malaysia - Kubas, Mohammed A.; Shabaruddin, Fatiha Hana; Mazlan-Kepli, Wardati; Jagan, Nirmala; Mohamed, Sahimi; Mohamed Nazar, Nor Ilyani; Zin, Che Suraya (Wolters Kluwer Medknow Publications, 2020)
Introduction: Non-vitamin K antagonist oral anticoagulants (NOACs), such as dabigatran and rivaroxaban, are now available for stroke prevention in patients with atrial fibrillation (AF) and are often clinically preferred over vitamin K antagonists (VKAs), such as warfarin. Data describing adherence and persistence to NOACs in real-life clinical practice in Malaysia are scarce. This study aimed to assess adherence and persistence to NOACs in patients with AF in two tertiary-care referral centers: Hospital Kuala Lumpur (HKL) and Hospital Serdang (HSDG). Materials and Methods: This was a retrospective cohort study that included all patients with AF who were treated with NOACs (dabigatran or rivaroxaban) in HKL and HSDG. Data were obtained from medical records and pharmacy databases. Adherence was assessed using proportion of days covered (PDC) over a 1-year duration. High adherence was defined as PDC ≥80%. A gap of >60 days between two consecutive refills was used to define non-persistence. Result: There were 281 patients who met the inclusion criteria, with 54.1% (n = 152) male. There were 75.1% (n = 211) patients on dabigatran and others on rivaroxaban. Only 66.9% (n = 188) of patients achieved high adherence with PDC ≥80% and 69.8% (n = 196) were persistence with >60-day gap over 12 months. Adherence and persistence were both influenced by treatment center, whereas polypharmacy only influenced adherence. Conclusion: Overall adherence and persistence to NOACs were suboptimal and varied between treatment centers, potentially due to institution-specific administrative and clinical practice differences. Clinical care and outcomes can potentially be optimized by identifying factors affecting adherence and persistence and by implementing interventions to improving them